Energy landscapes of colloidal clusters: thermodynamics and rearrangement mechanisms. - Calvo, F; Doye, J; Wales, D (2012)
New experiments involving direct observation of colloidal clusters by optical microscopy promise to deliver a wealth of new information about such systems. Calculations suggest that some of the observable properties may be predicted using a simple pairwise potential to represent the interparticle forces, but in a range of parameter space that is distinctly different from previous representations of atomic clusters. The present contribution provides some benchmark calculations and predictions of structure, thermodynamics and rearrangement mechanisms for colloidal clusters containing up to 80 particles. The results suggest that distinct features characteristic of short-ranged interactions should be observable in terms of the structure, thermodynamics and dynamical properties. Analysis of a kinetic transition network for the 19-particle cluster reveals super-Arrhenius behaviour in the dynamics, analogous to a 'fragile' glass-former.